Keabsahan Klausula Perpanjangan Periode dalam Restrukturisasi Kredit Akibat Pandemi Covid-19 - Tamara Teguh (Fakultas Hukum Universitas Airlangga, 2021)
The Corona Virus Disease 2019 (COVID-19) outbreak was determined by the President as a non-natural disaster through Presidential Decree Number 12 of 2020 concerning the Designation of Non-Natural Disaster for the Spread of Corona Virus Disease 2019 (COVID-19) as a National Disaster. Its rapid spread has an impact on all aspects of human life, especially in the economic sector, many business actors have suffered losses and a number of banks are experiencing credit risk, which debtors or customers are unable to make credit installments on the pretext of being affected by the pandemic. The Presidential Decree cannot automatically cancel existing agreements, so that the Government makes policies in order to stimulate economic growth. This policy was issued by the Financial Services Authority through Regulation of the Financial Services Authority of the Republic of Indonesia Number 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy on the Impact of the Spread of Corona Virus Disease 2019 which has been extended by the Financial Services Authority Regulation of the Republic of Indonesia Number 48/POJK.03/2020 as an effort to avoid default. The debtor is given loan repayment relief at the Bank or Leasing with terms determined by the Bank. This payment relief is known as credit restructuring, which there is a renegotiation process to change existing loans. One of the changes in the agreement is by rescheduling, namely extending the installment payment period. Keywords: COVID-19 Disease Outbreak; Credit Restructuring; Rescheduling.Wabah penyakit Corona Virus Disease 2019 (COVID-19) ditetapkan oleh Presiden sebagai bencana non alam melalui Keputusan Presiden Republik Indonesia Nomor 12 Tahun 2020 Tentang Penetapan Bencana Non Alam Penyebaran Corona Virus Disease 2019 (COVID-19) Sebagai Bencana Nasional. Penyebarannya yang begitu pesat berdampak pada segala aspek kehidupan manusia terutama di bidang ekonomi, banyak pelaku usaha yang mengalami kerugian dan sejumlah perbankan mengalami risiko kredit, dimana debitur atau nasabah tidak mampu untuk melakukan pembayaran cicilan kredit dengan dalih terkena dampak pandemi. Dengan adanya Keputusan Presiden itu tidak dapat serta merta membatalkan perjanjian yang sudah ada, sehingga Pemerintah membuat kebijakan dalam rangka menstimulus pertumbuhan ekonomi. Kebijakan tersebut dikeluarkan oleh Otoritas Jasa Keuangan melalui Peraturan Otoritas Jasa Keuangan Republik Indonesia Nomor 11/POJK.03/2020 Tentang Stimulus Perekonomian Nasional Sebagai Kebijakan Countercyclical Dampak Penyebaran Corona Virus Disease 2019 yang telah diperpanjang dengan Peraturan Otoritas Jasa Keuangan Republik Indonesia Nomor 48/POJK.03/2020 sebagai upaya agar tidak terjadinya wanprestasi. Debitur diberikan keringanan pembayaran cicilan pinjaman di Bank atau Leasing dengan persyaratan-persyaratan yang ditentukan oleh Bank. Keringanan pembayaran ini dikenal dengan restrukturisasi kredit, dimana terdapat proses renegosiasi atau negosiasi ulang untuk merubah perjanjian kredit yang sudah ada. Perubahan perjanjian tersebut salah satunya ialah dengan penjadwalan kembali atau rescheduling, yaitu memperpanjang periode pembayaran cicilan.Kata Kunci: Wabah Penyakit COVID-19; Restrukturisasi Kredit; Penjadwalan Kembali.